Memória feminina sindical como forma de resistência: a luta das professoras do 17º núcleo do CPERS/Sindicato - Rosa, Diênifer Alves Ramos da (2019)
This research aims at understanding the meaning of Memory to a group of female teachers engaged in CPERS/ Sindicato. This is the second largest trade union institution in Latin America and it represents teachers, school employees and experts from the state network. With that said, the participants of this study are five teachers involved in the category strikes from 1979 to 1991. Through their own stories they brought to life memories from the historical period related to this research which served to answer the following objectives: understanding the meaning of Memory to this group of teachers while living with the current trade union crisis in Brazil, identifying characteristics related to the repression and discrimination imposed to this women due to their trade union performance; listing possible distinguished characteristics from a movement formed mainly by women; and at last, analyzing the relationship between the category and the state representatives on the present looking for prospects to the future struggles of the institution. In order to collect data a semi-structured interview was made with the participants through a questionnaire with ten open questions. This study takes into account the principles of Oral History and relevant literature (BULHÕES, 1992; SENNA e MATOS, 2011; HALBWACHS, 1990; amongst others). Regarding the results, it is possible to say that to the this group of women, Memory represents a possibility of resistance and reorganization of the trade union struggle on the present. Besides that, it became clear that the repression and discrimination endured by them presented itself in different ways; the state used to threaten them by putting their physical integrity at risk and provoked them through psychological terror, while part of the civilians tried to shame them on going back to their places, as mothers and housewives but never as activists. And if from a certain portion of the society they received this kind of treatment, within the trade union environment the situation was based on acknowledgement, union and resistance. That happen, according to them, due to them being a movement that consisted mainly on women who became friends and raised their kids within this context where they felt like belonging to and discover themselves. However, regarding the category relationship with the state representatives the teachers evaluate it mostly as negative and show a lack of hope in a change on the government's part. Nevertheless, since they know the history and the potential of Brazilian trade union movement, they bet all their cards on the idea that the change will only come through the reorganization, awareness and struggle from the working class.